STUDI PENURUNAN LIGNIN PULP JERAMI PADI MELALUI VARIASI WAKTU PEMASAKAN DAN KONSENTRASI NaOH - Ervie Sukma Prabawati; Ahmad M Fuadi; Denanda Putri Pratami; Nurul Izzaty; Fitri Lita Agustina; Yosita Dyah Anindita; Maja Pranata Marbun (Jurnal Teknik Kimia, 2025)
Abstract. Rice straw is one of the agricultural wastes that is only used for animal feed or simply discarded into the environment. The high cellulose content in rice straw allows this material to be used as the main source for pulp production. Pulp processing using the kraft process involves mixing the kraft process involves mixing rice straw raw materials with Na2S and NaOH cooking solutions. The concentration of the Na2S cooking solution was 4%, while the NaOH concentration varied between 0%, 1%, 3%, and 5% with cooking times of 30 minutes, 60 minutes, 90 minutes, and 120 minutes. After cleaning, the raw material was dried in an oven until its weight was constant. This study aims to determine how cooking time and the effect of sodium hydroxide concentration affect the low lignin level in rice straw using the kraft process. The results obtained from this process are the calculation of the kappa number and lignin content. Cooking was carried out for 30 minutes with a Na2S concentration of 4% and a NaOH concentration of 0%, and the highest lignin content was 3,057%. In 120 minutes of cooking at a concentration of 5% NaOH, the lowest lignin content was 0,898%.